Investing wisely to end hunger and strengthen agriculture, with no region left behind: Latin America - Andrade, Robert Santiago; Lopera, Diana Carolina; Rivera Vasco, Tatiana Carolina; Urioste, Sergio; Tohme, Joseph M.; González, Carolina (Bioversity International and the International Center for Tropical Agriculture, 2021)
Latin America and the Caribbean economies began to slow down and stagnate during the 2008 economic crisis. This situation has been aggravated by the current health crisis, which is expected to set back regional development by almost ten years. Projected gross domestic product (GDP) was expected to shrink by 9.1% by the end of 2020, falling to values similar to those observed in 2010. In addition, poverty has increased like never before in only one year, reaching an estimated total of 231 million people, about 38% of all the population, with almost two out of every five poor people living in extreme poverty, and who are more exposed to food insecurity. However, the extent of the current economic crisis is quite heterogeneous among countries. For some, it is coupled with pre-pandemic conditions of political instability, social unrest, high poverty rates, and extreme food insecurity. Countries from the Dry Corridor (El Salvador, Nicaragua, Honduras, and Guatemala) were already facing a continuing exodus of people trying to escape from their precarious economic situations aggravated by environmental disasters such as the recent hurricanes. Countries facing political instability and social unrest are likely to suffer more from the uncertainty in their economic systems and their populations are prone to leave, while areas with erratic climate conditions have had to deal with high-risk agriculture and face similar consequences. If no immediate actions are taken, this problem could be exacerbated, creating an even greater flow of outward migration, risking the region’s stability and its potential to become a major food producer for the world. Agriculture is one of the most relevant sectors for its potential to continue contributing to food security, poverty reduction, and resilience to counteract external shocks such as climate uncertainty or the current health crisis.